A political genealogy of Joseph Conrad - Ruppel, Richard J. (Richard Jeffrey), 1954- (Lexington Books, 2014)
In this comprehensive analysis, Richard Ruppel, a former president of the Joseph Conrad Society of America, reveals the radical contingency of the politics in Conrad's major fiction. A Political Genealogy of Joseph Conrad is the first full-length analysis of Conrad's politics since the 1960s.